1973
DOI: 10.1136/jmg.10.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Brachydactyly Associated with Hypertension

Abstract: Summary. A family showing brachydactyly associated with hypertension is reported. The number and location of the involved bones are quite different from the other cases with brachydactyly reported in the literature. Additionally, all our patients have high blood pressure. We believe that the disorder reported here represents a hitherto undescribed entity. It is thought that both hypertension and brachydactyly are transmitted as an autosomal dominant trait by a single pleiotropic gene or by two closely located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
2
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 1 publication
3
54
2
1
Order By: Relevance
“…This syndrome was described in a large Turkish pedigree, and includes severe hypertension and strokes in early life as well as brachydactyly (shortened fingers) and short stature (Bilginturan et al 1973). Luft and co-workers meticulously characterized these patients.…”
Section: Autosomal Dominant Hypertension With Brachydactylymentioning
confidence: 99%
See 1 more Smart Citation
“…This syndrome was described in a large Turkish pedigree, and includes severe hypertension and strokes in early life as well as brachydactyly (shortened fingers) and short stature (Bilginturan et al 1973). Luft and co-workers meticulously characterized these patients.…”
Section: Autosomal Dominant Hypertension With Brachydactylymentioning
confidence: 99%
“…Under these conditions, genetic abnormalities that markedly impact blood pressure variation should also materialize as stroke genes. For monogenic forms of hypertension, several reports of increased stroke frequency exist, including hypertension with brachydacytly (Bilginturan et al 1973), glucocorticoid remediable hypertension (Rich et al 1992;Litchfield et al 1998), apparent mineralocorticoid excess (New et al 1977), and Gordon's syndrome (PHA2).…”
Section: Hypertension and Strokementioning
confidence: 99%
“…5 The sole exception is autosomal-dominant hypertension with BDE (HTNB, OMIM #112410), first reported in a Turkish kindred. 2,6 HTNB was linked to chromosome 12p in six unrelated families. 2,7,8 The locus accounts for a ~50 mm Hg mean blood pressure difference at age 50 years.…”
mentioning
confidence: 99%
“…Bilginturan et al 1 first described the syndrome of severe autosomal dominant hypertension and brachydactyly. 1 The gene responsible for the syndrome was mapped to chromosome 12 p. 2 Magnetic resonance tomography showed that all 15 affected family members tested had a left-sided loop of the posterior inferior cerebellar artery (PICA) impinging on the rostral ventrolateral medulla, compared to none of 11 non-affected family members.…”
Section: Introductionmentioning
confidence: 99%
“…1 The gene responsible for the syndrome was mapped to chromosome 12 p. 2 Magnetic resonance tomography showed that all 15 affected family members tested had a left-sided loop of the posterior inferior cerebellar artery (PICA) impinging on the rostral ventrolateral medulla, compared to none of 11 non-affected family members. 3 Animal studies have shown that pulsatile compression of the rostral ventrolateral medulla increases blood pressure.…”
Section: Introductionmentioning
confidence: 99%